Identificación de Marcadores TRA-l-60, OCT-4, NANOG y S SEA-4 en Muestras de Células Madre Cancerosas de Pacientes Diagnosticados con Cáncer Oral (2022)
Introduction: Oral cancer can result from a primary lesion or originate from another distant or adjacent tumor lesion leading to malignant neoplasms in the structures and tissues of the oral cavity (metastasis). Objective: To identify TRA-I-60, OCT-4, NANOG and S SEA-4 markers in cancer stem cells of patients diagnosed with oral cancer. Materials and Methods: It corresponds to an experimental type research, by Immunofluorescence method, 5 μm slices will be routinely deparaffinized and then rehydrated. antigenic recovery will be performed in buffer 10 mm citrate buffer, Ph 6.0 for 15 minutes in an electric pressure cooker. the slides will be incubated in H2O2 1% for 15 minutes, to block endogenous peroxidase. Then 3% BSA will be used for one hour to block nonspecific binding. The sections will be incubated overnight at 4°C with the corresponding primary antibody (antiTral-60, anti-OCT-4, anti-NANOG, anti-S SSE-4), at a 1:100 dilution in 1% BSA. Results: OCT 4 marker manifested with higher intensity in well-differentiated cancer, SSEA4 marker increases with tissue dedifferentiation and NANOG and TRA-1-60 markers remain constant during tumor progression. Conclusions: Of the different markers analyzed related to progenitor cells, all were found in the patient samples, indicating among them more evident marker differences.